Soil pH - nutrient relationships: the diagram - Hartemink, Alfred E.; Barrow, N. J. (Plant and soil, 2023)
The pH of the soil in relation to the availability of plant nutrients has been an important research topic in soil fertility and plant nutrition. In the 1930 and 1940 s, a diagram was proposed that showed how the availability of major and minor nutrients was affected by the pH. This conceptual diagram, developed by Emil Truog based on earlier work, included 11 nutrients. The width of the band at any pH value indicated the relative availability of the plant nutrient. The band did not present the actual amount, as that was affected by other factors such as the type of crop, soil and fertilization. For the 11 nutrients on the diagram, a pH of around 6.5 was considered most favorable. The diagram has been often published in text books and soil extension material and continues to be reproduced. This paper reviews how the diagram was developed, and what its limitations are. In recent decades, research in soil fertility and plant nutrition has focused on the biological transformations of plant nutrients in the soil and it has been recognized that the soil pH influences solubility, concentration in soil solution, ionic form, and adsorption and mobility of most plant nutrients. Nutrients interact and different plants respond differently to a change in pH. The soil pH cannot be used to predict or estimate plant nutrient availability, and the diagram should not be used as it suffers from numerous exceptions and barely represents any rules.